Dilemmas of Transcultural Mobility in M. G. Vassanji’s The Assassin’s Song - Vandana Sukheeja; JapPreet Kaur Bhangu (Asiatic: IIUM Journal of English Language and Literature, 2023)
The contemporary trend in migration has transformed the world into a space without borders with multiple crossings across national and international boundaries taking place. It has given rise to what Gilles Deleuze and Felix Guattari characterise as deterritorialisation and reterritorialisation, which, in turn, affects the process of identity constitution and establishing of home. Often it gives rise to a conflict between reality and aspirations, responsibilities and desires. The present paper explores ideas related to transcultural mobility and its impact on identity and belonging as portrayed in M. G. Vassanji’s The Assassin’s Song (2007). Vassanji in the novel creates a transcultural space to examine dilemmas around the concept of roots, as identity travels on other routes in search of better lives and fulfilment of aspirations. The paper examines how mobility empowers even as relationships change with home and with those left behind.